2016
DOI: 10.2298/apt1647001d
|View full text |Cite
|
Sign up to set email alerts
|

Barley grain enrichement with essential elements by agronomic biofortification

Abstract: Barley grain is rich in mineral nutrients, but their bioavailability to humans depends on antinutrients that restrain bioavailability and promoters that promote bioavailability. The aim of this study was to examine composition of barley grain, including phytate and phenolics as antinutrients, carotenoids and glutathione as promoters and mineral elements, such as Ca, Mg, Fe, Si, Zn and Mn influenced by various non-standard foliar fertilizers (Zircon, Chitosan, Siliplant, Propikonazole), includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…After the summer harvest, we assessed crop yield (at 14% grain moisture; kg ha -1 ) and determined different chemical ingredients in barley grain. The results (Dragičević et al, 2016a) indicate that the timing of treatment (year) affected barley grain yield and chemical composition, and the highest impact was found for Si under unfavourable conditions. The applied treatments were most effective regarding grain yield and increase in grain quality, mainly by reducing the Pphy/β-carotene ratio and increasing GSH content, thus increasing the potential bioavailability of the examined mineral elements.…”
Section: Field Treatment Of Other Crops With Brasinosteroids: Effectsmentioning
confidence: 95%
See 3 more Smart Citations
“…After the summer harvest, we assessed crop yield (at 14% grain moisture; kg ha -1 ) and determined different chemical ingredients in barley grain. The results (Dragičević et al, 2016a) indicate that the timing of treatment (year) affected barley grain yield and chemical composition, and the highest impact was found for Si under unfavourable conditions. The applied treatments were most effective regarding grain yield and increase in grain quality, mainly by reducing the Pphy/β-carotene ratio and increasing GSH content, thus increasing the potential bioavailability of the examined mineral elements.…”
Section: Field Treatment Of Other Crops With Brasinosteroids: Effectsmentioning
confidence: 95%
“…Based on previous field trials on one fruit (apple) and two field crops (soybean and barley), we concluded that, when compared with other non-standard fertilizers, the preparation based on 24-EBL has effect on the quality and chemical composition of crops, rather than on their yield (Nikolić & Waisi 2012;Dragičević et al 2016a, b), and it acts to protect crops under stressful conditions (Stevanović et al 2012).…”
Section: Field Treatment Of Other Crops With Brasinosteroids: Effectsmentioning
confidence: 95%
See 2 more Smart Citations
“…After summer harvest we assessed the yield (at 14% grain moisture content; kg ha -1 ) and determined different chemical ingredients in barley grain using standard methods (Tables 8 and 9). The results (Dragičević et al, 2016a) indicated that the year affected barley grain yield and its chemical composition, and the highest impact was found for Si under unfavourable conditions (data not shown). The applied treatments had the highest effectiveness on grain yield and increased grain quality, mainly through a reduction in P phy / β-carotene ratio (Table 9) and increase in GSH content (data not shown), thus increasing potential bioavailability of the examined mineral elements.…”
Section: Survey Of Results and Discussionmentioning
confidence: 98%